The forbidden towers - Gaskin, Carol; Price, T. Alexander ([Mahwah, N.J.] : Troll, 2003)
As Lifin, a young elf, the reader makes decisions controlling his search through the five Forbidden Towers for the herb that will cure his people of the eleven plague.
Keywords: Children's stories, American; Plot-your-own stories; Fantasy fiction